Enhanced short chain fatty acids production from anaerobic fermentation of primary sludge using free ammonia pretreatment. (20th February 2023) - Zhang, Jiamin; Wang, Dongbo; Li, Xiaoming; Liu, Xuran; Yang, Qi; Xu, Qiuxiang; Yang, Guojing; Duan, Abing; Fang, Yingchun
Abstract: This study is the first to report a new free ammonia (FA) pretreatment technique to recover short-chain fatty acids (SCFAs) from primary sludge (PS). The results showed FA pretreatment (240 mg N/L) largely enhanced the SCFAs production from PS to 355.8 mg chemical oxygen demand (COD)/g VSS, which was about 4.5-fold that of control (i.e., 80 mg COD/g VSS). Mechanism investigations showed that FA pretreatment greatly accelerated the PS solubilization and destroyed the integrity of EPS, and the easily biodegradable substrates in the fermentation broth increased significantly, providing microorganisms with more organics to convert into SCFAs. Further analyses displayed that FA greatly inhibited the methane production during fermentation, resulting in further accumulation of SCFAs. Given that the NH4 + -N released during the fermentation can be converted into FA in situ, this could facilitate the transition of wastewater treatment plants operation from linear to circular mode. Graphical abstract: Image 1 Highlights: FA greatly increased the production of SCFAs by about 4.5 times that of the control. The optimum concentration of FA pretreatment was 240 mg/L with the SCFAs yield of 355.8 mg COD/g VSS. FA facilitated the disintegration and biodegradability of PS and inhibited methane production. FA pretreatment could be applied to PS alone and a mixture of WAS and PS.